Katalog zbirke velikih krešičev (Carabus) v zbirki CBKS (Coleoptera: Carabidae: Carabinae: Carabini) - Kofler, Bojan (Acta entomologica slovenica (Ljubljana), 2013)
Previously unpublished data on the distribution of the species of the genus Carabus Linnaeus in Slovenia are presented. The specimens are preserved in the private collection CBKS (Collection Bojan Kofler, Škofja Loka), where 20 species out of 27 known in Slovenia are represented: C. arvensis from 4, C. catenulatus from 28, C. ullrichi from 4, C. granulatus from 10, C. cancellatus from 14, C. glabratus from 3, C. hortensis from 11, C. alpestris from 5, C. carinthiacus from 2, C. sylvestris from 3, C. convexus from 8, C. intricatus from 1, C. creutzeri from 21, C. irregularis from 6, C. variolosus from 8, C. caelatus from 7, C. croaticus from 6, C. germari from 44, C. coriaceus from 27 and C. gigas from 2 localities.
Keywords: Carabidae; Carabus; Coleoptera; faunistics; favna; Slovenia; Slovenija